A SYSTEMATIC REVIEW OF THE ROLE OF REGIONAL AVIATION IN THE AIRFREIGHT INDUSTRY - Kille, Tarryn; Bates, Paul; Murray, Patrick S. (Science-based technologies, 2014)
The purpose of this article is to explore the themes and challenges for regional aviation regarding the provision of airfreight services. The systematic review highlights three major challenges affecting the regional airfreight sector including: integration; infrastructure; and service reliability. There is a considerable dearth of academic literature available in this area. Thus, this paper aims to assist in highlighting these gaps and illustrating the potential for future research opportunities. It is hoped that this work will assist policy-makers, supply chain and air transport industry representatives as they seek to overcome the challenges hindering the development of regional aviation.